ADVANCING THE POTENTIAL OF PET AND PP-BASED BEVERAGE PACKAGING TO SUPPORT CIRCULAR ECONOMY - Trisyanti, Dini; Ranggi Laksita Wengi, Khair; Rachmawati, Rizka Legita; Akib, Rangga (UI Scholars Hub, 2022)
With around 5.6 million tons of annual plastic consumption and merely 7 percent plastic recycling rate, Indonesia is facing a plastic pollution crisis. The recent progress of Indonesia’s recycling industries has provided an asset to address this crisis. In 2017, the domestic post-consumption plastic waste could only fulfil around 24 percent the domestic needs for recycled plastic, which stands at 1.65 million ton/year. Leveraging the plastic waste ‘asset’ through circular economy can fill this demand gap. A five-month study was conducted to analyse the recycling rate of Polyethylene terephthalate (PET) and Polypropylene (PP)-based beverage plastic packaging in Greater Jakarta Metropolitan Area to see their potential in fostering circular economy. Structured interview involving 385 upstream and downstream recycling actors in Greater Jakarta Metropolitan Area provided primary data for the study. While secondary data from previous studies, academic journals, Nielsen’s audit data and electronic sources complement the primary data, particularly regarding recycling actors and packaging consumption rate. The study showed that over 329 tons of beverage plastic packaging waste was collected daily in Greater Jakarta Metropolitan Area, in which PET-based packaging had accounted for 78 percent of them. Waste pickers play a key role here by contributing to 65% of the collected PET waste. The study also showcased a mature recycling chain of PET and PP-based packaging with its recycling rate that reaches 74 to 93 percent. Looking at their economic value, PET and PP contributed 30 to 51 percent to the income of waste collectors. It can also be estimated that economic activities related to PET management in the could generate IDR 700 million per day at collector level only. The demands of PET continue to increase following the growing innovation in PET-based products. An effectively managed PET and PP plastic system could simultaneously address this demand and foster circular economy.